2019
DOI: 10.1039/c9ra01741k
|View full text |Cite
|
Sign up to set email alerts
|

Triple phase boundary and power density enhancement in PEMFCs of a Pt/C electrode with double catalyst layers

Abstract: Pt/C double catalyst layers (DCL), serving as an anodic electrode, have been utilized in a PEMFC application for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…Water is produced and must be drained to the BP via the GDL to prevent cathode flooding. Conversely ionomer channel enables protons to migrate from the membrane while electronically conductive network (carbon and metal) ensures the electron transport from the electric load via BP and GDL [23,24]. The non-catalyzed ORR is slow.…”
Section: The Electrode Active Layer (Al)mentioning
confidence: 99%
“…Water is produced and must be drained to the BP via the GDL to prevent cathode flooding. Conversely ionomer channel enables protons to migrate from the membrane while electronically conductive network (carbon and metal) ensures the electron transport from the electric load via BP and GDL [23,24]. The non-catalyzed ORR is slow.…”
Section: The Electrode Active Layer (Al)mentioning
confidence: 99%
“…Then, this method was further improved by the rational design of a dual-functional catalyst layer with different hydrophilic/hydrophobic features (Figure A), showing better water management capabilities . Recently, Dao et al confirmed the enhancement of TPBs and the PEMFC performance with the double catalyst layer (DCL) design shown in Figure B, realized by a new spray and electrophoresis (EPD) method . Other attempts have also been made by synthesizing nanostructured or doped carbon substrates for Pt loading.…”
Section: Game Changers: Improved Transport Pathways Engineered By Nov...mentioning
confidence: 99%
“…Preparation processes of a dual-layer-structured catalyst layer by the (A) high-temperature direct spray deposition method and (B) spray + EPD method, (C) ORR kinetics and transport processes for the carbon substrate with different pore structures, and (D) precise dispersion of both the ionomer and Pt realized by the N doping of the carbon substrates …”
Section: Game Changers: Improved Transport Pathways Engineered By Nov...mentioning
confidence: 99%
See 1 more Smart Citation
“…The ECSA values were calculated from the hydrogen adsorption region in the negative-going potential scan of the CVs. 17,18 The utilization efficiency of the Pt/BiPyPBI/ CB catalyst was then determined to evaluate the preparation process of the catalyst in comparison to the commercial Pt/CB catalyst (see Table 1). 19 The specic surface area (SSA) was determined from the following equation.…”
Section: Electrochemical Surface Area (Ecsa) and Oxygen Reduction Reamentioning
confidence: 99%